Rethinking the Role of Visegrad Group in the EU Enlargement Process - Muhammad Anugrah Utama; Allysa Ramadhani (Intermestic: Journal of International Studies, 2022)
The rise of authoritarianism and European Union (EU) skepticism in Central Europe has raised concern about the EU Integration project. Populist movements in Visegrad Group countries, consisting of four Central European states, have been deemed threats to the Integration project and the EU enlargement process. This paper attempts to revisit and rethink the role of the Visegrad Group in EU integration policy and process using a case study of the role of V4 cooperation with six Western Balkan Countries (WB6) through the socio-constructivist lens. This paper finds the potential of socio-constructivism in explaining the aspect of norms, values, and identities, not just material interests. Moreover, the V4 countries also support WB6 as an example of sub-regionalism as a means to EU membership. In the end, this paper attempts to map out the characteristics, prospects, and impediments of V4’s role in supporting the WB6’s path to the EU.